Design And Fabrication Of Spin Coating System For 8-Inch Wafer - Teoh, Chin Keng (Universiti Sains Malaysia, 2018)
The size of the silicon wafer has been increased from 100 mm to 200 mm in diameter. The transition of the wafer into bigger size is due to overall cost benefits resulting from the larger number of dice per wafer. Growing in chip size and growing of demand also reasons the transition wafer into the bigger size. A new equipment, spin coater system is developed to spin coat a wafer that can up to size 200 mm or 8-inch. The SMC rotary joint is used in this work to connect vacuum pipe and rotating chuck. The vacuum system is driven by a powerful motor. Both of the motor system and vacuum system are equipped with pulley and connected by a tendon matte belt. Pulse width modulation (PWM) is used to control the speed of the motor while infra-red (IR) sensor is used to track the rotation speed. The spinning rate of the spin coater system varies between 500 rpm to 3000 rpm. A thin film is coated on a glass substrate and thickness of thin film recorded to test the function ability of the spin coater system. The spin coater system that developed has ability to coat a wafer that size can up to 200 mm and the speed is adjustable.